2021
DOI: 10.3390/app11177933
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Porosity Change in Bentonite Caused by Decay Heat on Radionuclide Transport through Buffer Material

Abstract: Bentonite is used as a buffer material in most high-level radioactive waste (HLW) repository designs. Smectite clay is the main mineral component of bentonite and plays a key role in controlling the buffer’s physical and chemical behaviors. Moreover, the long-term functions of buffer clay could be lost through smectite dehydration under the prevailing temperature stemming from the heat of waste decay. Therefore, the influence of waste decay temperatures on bentonite performance needs to be studied. However, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Elevated temperatures can have an impact on bentonite and its engineering properties. For example, simulations of high-discharge waste disposal in China have shown that thermal swelling and saturation processes may affect a tank stability for long periods [52], as higher temperatures can provoke montmorillonite dehydration [53]. The effect of temperature on the swelling pressure is highly controversial.…”
Section: Effect Of Temperature On the Swelling Pressurementioning
confidence: 99%
“…Elevated temperatures can have an impact on bentonite and its engineering properties. For example, simulations of high-discharge waste disposal in China have shown that thermal swelling and saturation processes may affect a tank stability for long periods [52], as higher temperatures can provoke montmorillonite dehydration [53]. The effect of temperature on the swelling pressure is highly controversial.…”
Section: Effect Of Temperature On the Swelling Pressurementioning
confidence: 99%
“…Several countries, including China, Switzerland, Belgium, and France, have framework their radioactive waste storage systems by leveraging expansive clay or swelling clay such as Bentonite as natural sealing (or capping layer), buffer material, or engineered clay barriers in nuclear repository systems, particularly deep geological repositories [5,6]. The applicability of these soils is determined by their unique qualities, which include very low hydraulic conductivity (impermeable), high swelling capacity, radioactive sorption capacity, microporous structure, and the ability to isolate waste for an adequate amount of time (≥100,000 years) [7].…”
Section: Introductionmentioning
confidence: 99%